2014
DOI: 10.1371/journal.pone.0113228
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Exposure Alters Proopiomelanocortin Gene Expression and Hypothalamic-Pituitary-Adrenal Axis Function via Increasing MeCP2 Expression in the Hypothalamus

Abstract: Proopiomelanocortin (POMC) is a precursor gene of the neuropeptide β-endorphin in the hypothalamus and is known to regulate various physiological functions including stress response. Several recent reports showed that fetal alcohol exposure programs the hypothalamus to produce lower levels of POMC gene transcripts and to elevate the hypothalamic-pituitary-adrenal (HPA) axis response to stressful stimuli. We investigated the role of methyl CpG binding protein (MeCP2) in the effects of prenatal ethanol on POMC g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 47 publications
6
62
0
Order By: Relevance
“…Aza treatment did not elicit any increased expression of Pomc in control samples and Crf in AF samples as they have reduced levels of methylation. We and others previously reported that hypermethylated promoters recruit methyl CpG binding proteins to repress the transcription of Pomc and tumor suppressor genes (Gangisetty et al, 2014;Lopez-Serra et al, 2008). In our experiments, Aza elicited its effect on stress regulatory genes by reducing their methylation and increasing expression.…”
Section: Discussionsupporting
confidence: 59%
“…Aza treatment did not elicit any increased expression of Pomc in control samples and Crf in AF samples as they have reduced levels of methylation. We and others previously reported that hypermethylated promoters recruit methyl CpG binding proteins to repress the transcription of Pomc and tumor suppressor genes (Gangisetty et al, 2014;Lopez-Serra et al, 2008). In our experiments, Aza elicited its effect on stress regulatory genes by reducing their methylation and increasing expression.…”
Section: Discussionsupporting
confidence: 59%
“…Three studies from the same working group found that prenatal alcohol exposure associated with increased Pomc methylation in the rat hypothalamus, which in turn related to decreased gene expression [13,15,16]. These changes were maintained transgenerationally (up to three generations), but could be rescued by gestational choline supplementation.…”
Section: Prenatalmentioning
confidence: 99%
“…We do, however, highlight five genes that were investigated by multiple studies and, promisingly, showed a consistent direction of associations. In three rodent studies from the same working group [13,15,16], increased methylation and decreased expression of Pomc-a gene implicated in stress response, metabolism, and immune function-was observed in response to prenatal alcohol exposure across multiple tissues. These results highlight one mechanism through which fetal alcohol programming can occur, contributing to HPA axis dysregulation and increased addiction risk [16].…”
Section: Summary Of Study Characteristics and Findingsmentioning
confidence: 99%
See 2 more Smart Citations